2020
DOI: 10.1111/1750-3841.15378
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing oxidative stability of sunflower oil by supplementation with prickled broom (Pterospartum tridentatum) ethanolic extract

Abstract: This study aimed to evaluate the effect of ethanolic extract of Pterospartum tridentatum flowers in the stability of sunflower oil. The extract was characterized regarding to its antioxidant activity by the 2,2,1‐diphenyl‐1‐picrylhydrazyl (DPPH) scavenging method (EC50 = 76.3 ± 2.6 µg/mL) and total phenolic content (200 ± 8 mg GAE/g). Extracts were added at 500 mg/L (E1) and 1,000 mg/L (E2), and after 30 days of storage at room temperature, E2 oil showed improved quality parameters, with a reduction of 22.4%, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
16
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 37 publications
5
16
1
Order By: Relevance
“…So far, only several studies have been investigated the improvement of oxidative stability of sunflower oil by supplementation with natural extracts obtained from berries byproducts or various value-added products obtained from fruits processing wastes. However, the data obtained after TOTOX value calculation are in agreement with the results reported by other studies in which sunflower oil was supplemented with other types of extracts [4,34]. Neves et al [34] reported a TOTOX value of 69.30 after 27 h of heat exposure at 180 • C of the sunflower oil sample supplemented with 1000 ppm of ethanolic extract obtained from prickled broom.…”
Section: Total Oxidation (Totox) Valuesupporting
confidence: 88%
See 1 more Smart Citation
“…So far, only several studies have been investigated the improvement of oxidative stability of sunflower oil by supplementation with natural extracts obtained from berries byproducts or various value-added products obtained from fruits processing wastes. However, the data obtained after TOTOX value calculation are in agreement with the results reported by other studies in which sunflower oil was supplemented with other types of extracts [4,34]. Neves et al [34] reported a TOTOX value of 69.30 after 27 h of heat exposure at 180 • C of the sunflower oil sample supplemented with 1000 ppm of ethanolic extract obtained from prickled broom.…”
Section: Total Oxidation (Totox) Valuesupporting
confidence: 88%
“…However, the data obtained after TOTOX value calculation are in agreement with the results reported by other studies in which sunflower oil was supplemented with other types of extracts [4,34]. Neves et al [34] reported a TOTOX value of 69.30 after 27 h of heat exposure at 180 • C of the sunflower oil sample supplemented with 1000 ppm of ethanolic extract obtained from prickled broom. This finding is in agreement with our data, when TOTOX values of 69.75, respectively 66.72 were recorded in response to 12 h of heating at 180 • C of the sunflower oil sample supplemented with 800 ppm PBBE, respectively ABBE.…”
Section: Total Oxidation (Totox) Valuesupporting
confidence: 88%
“…AV reflects the degree of hydrolysis of the oil [ 28 ] and is used to indicate the oil’s rancidity [ 7 ]. AV denotes the extent of lipid hydrolysis [ 10 ] and hydroperoxide decomposition [ 5 ] into free fatty acids and carbonyl groups, respectively. PGG/BHT mixture had a superior anti-hydrolytic effect compared to PGG-800 ppm ( p < 0.05), and this inhibition was concentration-dependent ( p < 0.05) compared to the raw oil.…”
Section: Resultsmentioning
confidence: 99%
“…As described by Neves et al, the RI ( 20 ND) of oil samples was measured by a digital refractometer NR101 [ 5 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation